What Lurks Beneath: Lacrimal Gland Adenocarcinoma Dedifferentiation to Sarcomatoid Carcinoma - Farrah-Hani Imran,; Muthukumaran Guhan,; Enda Kelly,; Jegan Thanabalan,; Farizal Fadzil,; Faridah Hanum, (Faculty of Medicine, UKM Medical Centre, 2015)
This was a case of a young lady presenting with 10 year history of a mass in the right eye. It was found to be an adenocarcinoma of the lacrimal gland from histopathological biopsy. She underwent wide excision, orbital exenteration and reconstruction with a free rectus abdominis flap. Unfortunately, she had a tumour recurrence which was not controlled by radiotherapy and a second excision. The behavior of the tumour was aggressive, resulting in widespread metastases. She passed away within a year of her presentation. Of note, the histopathology report from the second excision turned out to be sarcomatoid carcinoma. This is described in the literature as dedifferentiation, or high grade transformation (HGT). Occurrence of dedifferentiation in salivary gland tumours is well-established, but not as well-described in lacrimal gland tumours. In this case, there was a severely delayed presentation of a lacrimal gland adenocarcinoma in a young person, which underwent dedifferentiation into a sarcomatoid carcinoma. This phenomena is associated with aggressive tumour biology behavior and poor prognosis, despite surgery and radiotherapy.